NLRP6: A Multifaceted Innate Immune Sensor. Issue 4 (April 2017) - Levy, Maayan; Shapiro, Hagit; Thaiss, Christoph A.; Elinav, Eran
Abstract : NLRP6, a member of the nucleotide-binding domain, leucine-rich repeat-containing (NLR) innate immune receptor family, regulates inflammation and host defense against microorganisms. Similar to other NLRs, NLRP6 not only participates in inflammasome formation, but is also involved in nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling regulation and facilitation of gastrointestinal antiviral effector functions. Additionally, NLRP6 contributes to the regulation of mucus secretion and antimicrobial peptide production, thereby impacting intestinal microbial colonization and associated microbiome-related infectious, autoinflammatory, metabolic, and neoplastic diseases. However, several of the mechanisms attributed to the functions of NLRP6 remain debatable, leaving open questions as to the relevant molecular mechanisms and interacting partners, and putative human relevance. We herein discuss recent findings related to NLRP6 activity, while highlighting outstanding questions and future perspectives in elucidating its roles in health and disease. Trends: NLRP6 is highly expressed in the small and large intestine, and has both inflammasome-dependent and -independent roles in the maintenance of intestinal homeostasis. NLRP6 inflammasome-induced interleukin (IL)-18 is modulated by microbial metabolites, and downstream IL-18 secretion induces an antimicrobial peptide program in intestinal epithelial cells that is critical to prevent dysbiosis. NLRP6 in sentinel goblet cells is required for mucus production, thereby preventing the invasion of enteric bacteria into the mucosal layer in an inflammasome-dependent, but IL-18-independent manner. In association with the helicase DHX15, NLRP6 is involved in antiviral responses upon viral RNA sensing, in an inflammasome-independent manner. In myeloid cells, NLRP6 negatively regulates NF-κB signaling and thereby suppresses inflammatory responses.